К истории новогрудской редакции Пролога (на материале списков сентябрьского полугодия) - Чистякова, Марина Владимировна Владимировна (Slavistica Vilnensis, 2011)
Marina ChistiakovaOn the history of the Navahrudak edition of the Simple Synaxarion (on the basis of copies for the September haft of the year)The article is devoted to the analysis of the structure of the Navahrudak edition of the Simple Synaxarion on the basis of two manuscript synaxaria for the September half of the ecclesiastical year: Russian State Library, Museum collection, no. 4102, first quarter of the 16th century, and the Wróblewski Library of the Lithuanian Academy of Sciences, F 19–95, 1512. Their comparison revealed a number of common features (certain additional instructive stories, the Vita of the Three Vilnius Martyrs, the cycle of 10 stories about the Kievan Caves monks) which allow us to assume, that the two manuscripts represent the Navahrudak edition, but this is true only for their main part from 1st September till 3rd February. In the concluding part, from 4th February onward, the manuscript F 19–95 represents the expanded edition of the Simple Synaxarion, while the codex Mus. 4102 combines the same version with the short edition of the Simple Synaxarion. Apparently, a defective copy of the Navahrudak edition has been used while compiling the two manuscripts.